Numerical Modeling and Experimental Study on the Material Removal Process Using Ultrasonic Vibration-Assisted Abrasive Water Jet - Cheng, Zhichao; Qin, Shikang; Fang, Zhufang (Frontiers in Materials, 2022)
Currently, micro-abrasive water jet machining has the problem of insufficient processing capacity in the central area. To assist with improving the processing efficiency, ultrasonic vibration is introduced. First, based on the computational fluid dynamics method, the mathematical model of the three-dimensional shape prediction of micro-holes is established using a mixed model, standard k-ε model, discrete phase model, and dynamic mesh model. The effects of the ultrasonic vibration on the static pressure, jet velocity field, abrasive particle motion state, and material erosion rate in the stagnation zone are studied. Then the accuracy of the prediction model is verified by comparing the two-dimensional section of the experimental data and the simulated data and calculating the three-dimensional mean square deviation. The established prediction model is used to further analyze the optimal frequency of the ultrasonic vibration and the specific influence of the optimal amplitude on the machining effect in micro-abrasive water jet machining. The above research results have profound guiding significance for determining how to use ultrasonic vibration in micro-abrasive water jet machining.